Discovering Doris Lessing: convergences between Islam and her thoughts - Hasan, Md. Mahmudul (The International Institute of Islamic Thought, 2016)
The 2007 Nobel literature laureate Doris Lessing (1919-2013) is one of the twentieth century’s most prolific and versatile British writers. Her literary career is marked by the robustness and diversity of her ideas. The plurality of voices in her work makes room for discovering a very different Lessing from how she is usually construed and for discussing some of her views in a new and somewhat unusual light. In this study, I intend to look at her thoughts on education, literature, racism, and women’s rights and locate possible commonalities between them and certain facets of Islamic thought. As she is considered a humanist, a secular writer of great stature, the “grande dame” of British writing of her time, and handles explicit sexual relationships, a sense of remoteness and incomprehension is perhaps palpable in any attempt to discover an “Islamic Doris Lessing.” However, given that she is known for her courage and outspokenness, as well as for making unconventional moves and iconoclastic statements sometimes at the expense of her literary reputation, it will be interesting to see her ideas from an Islamic perspective.